H2O2 production rate in Lactobacillus johnsonii is modulated via the interplay of a heterodimeric flavin oxidoreductase with a soluble 28 Kd PAS domain containing protein - Valladares, Ricardo B.; Graves, Christina; Wright, Kaitlyn; Gardner, Christopher L.; Lorca, Graciela L.; Gonzalez, Claudio F. (Frontiers in Microbiology, 2015)
Host and commensals crosstalk, mediated by reactive oxygen species (ROS), has triggered a growing scientific interest to understand the mechanisms governing such interaction. However, the majority of the scientific studies published do not evaluate the ROS production by commensals bacteria. In this context we recently showed that Lactobacillus johnsonii N6.2, a strain of probiotic value, modulates the activity of the critical enzymes 2,3-indoleamine dioxygenase via H2O2 production. L. johnsonii N6.2 by decreasing IDO activity, is able to modify the tryptophan/kynurenine ratio in the host blood with further systemic consequences. Understanding the mechanisms of H2O2 production is critical to predict the probiotic value of these strains and to optimize bacterial biomass production in industrial processes. We performed a transcriptome analysis to identify genes differentially expressed in L. johnsonii N6.2 cells collected from cultures grown under different aeration conditions. Herein we described the biochemical characteristics of a heterodimeric FMN reductase (FRedA/B) whose in vitro activity is controlled by LjPAS protein with a typical Per-Arnst-Sim (PAS) sensor domain. Interestingly, LjPAS is fused to the FMN reductase domains in other lactobacillaceae. In L. johnsonii, LjPAS is encoded by an independent gene which expression is repressed under anaerobic conditions (>3 fold). Purified LjPAS was able to slow down the FRedA/B initial activity rate when the holoenzyme precursors (FredA, FredB and FMN) were mixed in vitro. Altogether the results obtained suggest that LjPAS module regulates the H2O2 production helping the cells to minimize oxidative stress in response to environmental conditions.